Reformulation of the Legal Politics of Restorative Justice in Handling Minor Criminal Offenses under Law Number 1 of 2023 on the Criminal Code - Muhammad Ridho Hakiki; Angkasa Angkasa; Abdul Haris Semendawai (Interdiciplinary Journal and Hummanity (INJURITY), 2026)
The enactment of Law Number 1 of 2023 on the Criminal Code marks a significant shift in Indonesia’s criminal law reform, including the implicit recognition of restorative justice within sentencing policy. This condition reflects the absence of a coherent legal policy framework that positions restorative justice as an integral component of national criminal law policy; instead, it continues to be treated primarily as an alternative or administrative practice rather than a formally institutionalized legal mechanism. This study employs a normative juridical research method, utilizing both statutory and conceptual approaches to examine the implementation of restorative justice in the treatment of minor offences under the newly enacted Criminal Code. The analysis is grounded in the legal system theory framework, encompassing legal substance, legal structure, and legal culture, to identify structural factors contributing to the suboptimal effectiveness of restorative justice in Indonesia. The findings demonstrate that restorative justice has not been explicitly institutionalized within the Criminal Code, resulting in legal uncertainty, fragmented institutional practices, and continued reliance on the discretionary authority of law enforcement officials. Furthermore, this study challenges the conventional assumption that restorative justice undermines the deterrent function of criminal law. It argues that, when properly designed and subject to adequate oversight, restorative justice can generate moral, social, and psychological deterrent effects that are more proportionate and effective in addressing minor offences than fear-based punitive sanctions.